2007
DOI: 10.1002/pts.804
|View full text |Cite
|
Sign up to set email alerts
|

Structure and gas transmission characteristics of microperforations in plastic films

Abstract: Bright fi eld transmitted light microscopy (BFTLM), differential interference contrast light microscopy (DICLM), conventional scanning electron microscopy (SEM) and low-vacuum scanning electron microscopy (LV-SEM) were used to observe microperforations in plastic fi lm used for modifi ed atmosphere packaging. Characteristics of the microperforations, including size, shape and obstructions are indicators of consistency and reproducibility of the process used to produce the microperforations. In addition, the mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(16 citation statements)
references
References 18 publications
1
15
0
Order By: Relevance
“…In the case of CO 2 concentrations, values of 22.1, 15.1, and 14.4 kPa were found in M5, M10, and M20 treatments, respectively (HSD ¼ 3.3 kPa). This situation was in accordance with the reports of Makino et al (2008), Allan-Wojtas et al (2007), and Ozdemir et al (2005), who demonstrated that the use of microperforation is an effective manner of controlling permeability in container walls and gas concentrations inside packages of modified atmosphere systems. Besides, treatments M0 and M5 were applied during a storage of 30 days and, consistently, the O 2 concentration was different between them (P 0.05), where those non-perforated bags had values of 0 kPa during all the experimental period, while in bags with five perforations the O 2 ranged between 0.5 and 3.0 kPa, with an average value of 1.7 kPa (Table 2).…”
Section: O 2 and Co 2 Concentrations Inside Packagessupporting
confidence: 92%
See 1 more Smart Citation
“…In the case of CO 2 concentrations, values of 22.1, 15.1, and 14.4 kPa were found in M5, M10, and M20 treatments, respectively (HSD ¼ 3.3 kPa). This situation was in accordance with the reports of Makino et al (2008), Allan-Wojtas et al (2007), and Ozdemir et al (2005), who demonstrated that the use of microperforation is an effective manner of controlling permeability in container walls and gas concentrations inside packages of modified atmosphere systems. Besides, treatments M0 and M5 were applied during a storage of 30 days and, consistently, the O 2 concentration was different between them (P 0.05), where those non-perforated bags had values of 0 kPa during all the experimental period, while in bags with five perforations the O 2 ranged between 0.5 and 3.0 kPa, with an average value of 1.7 kPa (Table 2).…”
Section: O 2 and Co 2 Concentrations Inside Packagessupporting
confidence: 92%
“…With this strategy, the permeability of plastic walls has been controlled (Allan-Wojtas, Forney, Moyls, & Moreau, 2007;Makino et al, 2008), and products like pre-cut Welsh onions (Ibaraki, Ishii, Ikematsu, Ikeda, & Ohta, 2000) and Charentais-type muskmelons (Rodov et al, 2002) have been handled properly in modified atmosphere, because the excessive O 2 drop inside the package has been avoided. Hence, the objective of the present study was to evaluate the effect of microperforation and temperature on the postharvest shelf life of MA-packaged huitlacoche.…”
Section: Introductionmentioning
confidence: 99%
“…In terms of enhancing the permeability of the film, many recent studies have focused on the perforation of the packaging films. Microperforation has been found to be an alternative approach for increasing the oxygen permeability or breathability of plastic films, especially in the applications where package surface area for gas exchange is limited . Various methods or technologies for perforating plastics films are known.…”
Section: Introductionmentioning
confidence: 99%
“…(McHugh et al 1996;Miller and Krochta 1997;Shit and Shah 2014). For the packing of fresh produce such as fruits and vegetables, LDPE packaging is typically microperforated for sufficient gas and water vapour transfer (Allan-Wojtas et al 2008). Because of the higher WVP and OP values, the present flaxseed mucilage-based seed film could be further developed as an alternative to packing fresh produce with less microperforation.…”
Section: Barrier Propertiesmentioning
confidence: 99%